Factors Related to Motor Development in Toddlers Aged 2-3 Years at Nagaswidak Health Center, Palembang - Eka Afrika; Arie Anggraini; Adelia Rahma Dhini; Alfina Fitria (Journal of Educational Innovation and Public Health, 2024)
Approximately 5-10% of children worldwide experience impaired motor development. Disrupted child development will contribute to morbidity that occurs throughout the child's life cycle, the transmission of poverty between generations, and in the long term can hold back the pace of a country's development. The purpose of this study was to determine the factors associated with motor development in toddlers aged 2-3 years at the Nagaswidak Health Center, Palembang. The research design used observational analytic with a cross-sectional approach. The population was all mothers who had toddlers aged 2-3 years in the Nagaswidak Health Center working area in January - March 2024, totaling 32 people. Sampling used the total population technique . Data analysis used the Spearman rank test. The results of the study obtained a relationship between knowledge and gross motor development (p value 0.080) and fine motor (p value 0.135), a relationship between gender and gross motor development (p value 0.144) and fine motor (p value 0.135), a relationship between nutritional status and gross motor development (p value 0.000) and fine motor (p value 0.003). There is a relationship between nutritional status and motor development, there is no relationship between knowledge and gender and motor development. It is expected that all related parties will increase stimulation for children related to motor development.